2023
DOI: 10.3390/f14051003
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Origin and Classification of Two Poplar Species on the Qinghai–Tibet Plateau

Abstract: Poplar not only has important ecological and economic value, but also is a model woody plant in scientific research. However, due to the rich morphological variation and extensive interspecific hybridization, the taxonomy of the genus Populus is very confused, especially in the Sect. Tacamahaca. Based on the extensive investigation of Populus on the Plateau and its surrounding areas, two taxa (Populus kangdingensis and Populus schneideri var. tibetica) that are very similar in morphology and habitat and are in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…However, as no discernible population growth was identified during the hybridization events, we suggest that this secondary contact might imply geographic expansion rather than population growth, as previous studies have indicated that geographic expansion and population expansion may not always be correlated (Excoffier et al 2009;Williams & Giddings 1984). Furthermore, some studies have suggested that hybridization events can occur despite continuous declines in overall population sizes (Pellegrino et al 2015;Shi et al 2023). In our study, even if restrictions 200 years ago prevented humans from colonizing forests for about seven years, this timeframe may not have been sufficient for the forest system to recover.…”
Section: Discussionmentioning
confidence: 56%
“…However, as no discernible population growth was identified during the hybridization events, we suggest that this secondary contact might imply geographic expansion rather than population growth, as previous studies have indicated that geographic expansion and population expansion may not always be correlated (Excoffier et al 2009;Williams & Giddings 1984). Furthermore, some studies have suggested that hybridization events can occur despite continuous declines in overall population sizes (Pellegrino et al 2015;Shi et al 2023). In our study, even if restrictions 200 years ago prevented humans from colonizing forests for about seven years, this timeframe may not have been sufficient for the forest system to recover.…”
Section: Discussionmentioning
confidence: 56%
“…All of these, together with the generally safe timber sales opportunities, made the production of hybrid poplars economical and profitable [4,5]. In addition, breeding has been going on all over Europe ever since [6,7], and poplars seem to be a good model for tree physiology and genomics research [8,9]. This shows that this issue is important across Europe and is still being addressed today. )…”
Section: Introductionmentioning
confidence: 99%
“…One major advantage of poplars and willows (Salix spp.) is that they have a relatively short cutting age, i.e., rotation time, to produce maximum yields of timber or fiber on a sustainable basis [8,9]. Taking into account their large volume, future poplar utilization should be based on an integrated and total use concept, i.e., produce the highest-value products or product combinations from each given raw material input so that nothing is wasted [17].…”
Section: Introductionmentioning
confidence: 99%